An update on the potential for male contraception: emerging options - Garside DA; Gebril A; Alsaadi M; Nimmo N; Mullen AB; Ferro VA (Dove Medical Press, 2013)
Deborah A Garside,1 Ayman Gebril,2 Manal Alsaadi,2 Natalie Nimmo,2 Alexander B Mullen,2 Valerie A Ferro2 1Imperial College London, Faculty of Medicine, London, 2University of Strathclyde, Strathclyde Institute of Pharmacy and Biomedical Sciences, Glasgow, UK Abstract: The human population continues to grow and is estimated to rise to 10.1 billion by the end of the century. Therefore, there is still an unmet need for safe and highly effective contraceptive options for both men and women. Current options available to men include withdrawal, condoms, and vasectomy. Methods in development fall into two categories: hormonal and nonhormonal. This review will provide an overview of the testosterone combinations and immunocontraception of hormonal targets. Nonhormonal immunocontraception of sperm proteins will also be examined, together with the use of agents to disrupt other sperm-associated targets and pathways. The categories focused on include epididymal proteins, testicular kinases, epigenetic reader proteins, opioids, lonidamine derivatives, retinoic acid, microRNAs associated with spermatogenesis, and plant extracts. Considering these developments, the number of options available to men is likely to increase in the near future. Keywords: hormonal, immunocontraception, nonhormonal contraceptives